THE EFFECT OF CSR HOTEL DEVELOPMENT ON MICRO BUSINESS POTENTIAL IN ENVIRONMENTAL CONSERVATION - Subarkah, Johny; Karsidi, Ravik; Diharjo, Kuncoro; Kartono, Drajat Tri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
Companies that are engaged in the tourism or hospitality industry sector are also not inferior to implement CSR activities. The development of CSR in the tourism sector, especially hotels, does not run as fast as other business sectors. Social responsibility is an important thing that needs to be considered for the progress of a country and region in particular. The research method used is quantitative. The data used are questionnaires distributed to customers and through direct interviews with farmers micro-entrepreneurs who are partners for Lorin Solo Hotels, Sahid Jaya Solo Hotels and New Kuta Hotels in Bali. The results of the study show that the Development of CSR Hotels has a significant positive effect on the Empowerment of Farmers Micro Enterprises in Environmental Conservation. This means that through the CSR hotel development activities carried out it will have a good effect and make the name of the hotel can be large in the eyes of the wider community and Micro Farmers also become more empowered. Keywords: Development of CSR Hotels, Empowerment of Farmers Micro Enterprises